PENDEKATAN ANTROPOLOGIS DALAM PARADIGMA USUL FIKIH - Dahlan, Moh. (Madania: Jurnal Kajian Keislaman, 2015)
Anthtropological Approach in the Paradigm of Islamic Legal Jurisprudence. Certain problems mainlyoccuring in almost Muslim societies appears to be so complex as it requires an alternative approach in ushulfiqh as a basis for developing a fiqh that is needed. Such alternative approach is adopted with paradigm ofanthropological ushul fiqh that offers an alternative anthropological studies to find out a solution and over comethe complicated paradigm of ushul fiqh in order to be contextual meaning. The Scientific theoretical frameworkused here is the paradigm of Karl Mannheim who divided the category paradigm of science into an ideologyand utopia and scientific paradigms of Muhammad Arkoun who classified Islamic scientific reasoning becomeslogical “Tradition with a big T” (at-Turâst bi harfin kabîr) and as a logical “tradition with small t” (at-turâs biharfin shagîr). Based on the result, the anthropological studies on the paradigm of ushul fiqh or fiqh will be ableto support the level of interconnection and dynamics among various schools of law. The aspect of general andparticular pattern will be dynamic and dialectic so that the development of legal jurisprudence may function wellin accordance with the public interests as well as the nation’s benefit